PENGEMBANGAN PARIWISATA BERBASIS PEMBERDAYAAN MASYARAKAT (COMMUNITY BASED TOURISM (CBT)) DI DESA WISATA NGARGORETNO, KECAMATAN SALAMAN, KABUPATEN MAGELANG - Yuliana Ari Widhianingsih; Nur Widiastuti; Muhammad Mathori (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This research is a qualitative research. The subjects in this research are 4 people consisting of 1 Ngargoretno Village apparatus, 1 Pokdarwis (Tourism Awareness Group) administrator of Ngargoretno Village, 1 tourist business citizen in Ngargoretno Village and 1 tourist. In conducting research on efforts to improve the development of community empowerment-based tourism (CBT) in the Tourism Village of Ngargoretno, Salaman District, Magelang Regency, Miles and Huberman qualitative data analysis method was used. The results of the study stated that the development of community-based tourism (CBT) in the Tourism Village of Ngargoretno, Salaman District, Magelang Regency still needs to be improved due to the lack of support in helping promote tourism villages, the lack of community in providing support to the village government in developing the village tourism, lack of budget from non-governmental organizations, lack of creativity from local communities to develop tourist villages. Efforts to develop Community Based Tourism (CBT) in the Tourism Village of Ngargoretno, Salaman District, Magelang Regency, namely collaborating with local governments, involving the community, seeking adequate budgetary support, conducting training for actors or managers of tourist village objects.